Biotecnologia associada ao óleo essencial de alecrim pimenta na ensilagem da biomassa a partir do consórcio de sorgo com o capim paiaguás - Santos, Sebastião de Jesus (2019)
The aim of this study was to assess the effect of the rosemary-pepper essential oil and the nanoformulated thymol on the microbiological and fermentation profile and the aerobic stability in the silage of the biomass of sorghum and Paiaguas palisadegrass. Four additives were assessed (control, rosemary-pepper essential oil, 62 and 100% purity nanoformulated thymol) associated with three times of opening the silo (15, 30 and 45 days), in the silage of sorghum with Paiaguas palisadegrass. A completely randomized experimental design was used in a 4 x 3 factorial scheme with five replications. The population of Clostridium was higher in the control treatment and with nanoformulated essential oil (NEO). Higher population of Lactobacillus was registered in the control treatment and a lower one with the addition of 62 and 100% nanoformulated thymol. The population of Lactobacillus decreased with the increase in the time of opening the silo. Higher aerobic stabilities were registered with the 100% nanoformulated thymol additive (time of opening 15 days) and with the 62% nanoformulated thymol (times of opening 30 and 45 days). The aerobic stability increased with the time of opening the silo. The use of 100% nanoformulated thymol resulted in higher losses of dry matter, gases, and effluents, while the use of NEO provided lower losses of dry matter and gases. Higher losses of dry matter, gases, and effluents were registered at the time of opening the silo at 45 days. The nanoformulated thymol was more efficient at controlling the populations of Clostridium and Lactobacillus and also improved the aerobic stability of the Sorghum with Paiaguas palisadegrass.